Kinetics And Kinematics Determinations Of Martial Arts Performers Using 3d Motion Capture Camera - Awang Soh@ Yusoff, Ahmad Afiq Sabqi (2021)
A motion Capture camera is the process of recording movements of real-life through a computer. Many studies have been conducted to broaden the use of this optical motion camera such as in animation, surveillance, sports mechanics, and clinical applications. MOCAP system is constantly being upgraded throughout the year, from media arts applications to more cutting-edge technology applications ensuring that this technology will never become obsolete. Hence this main objective was put to test in measuring the performer dynamic movement using MOCAP by introducing SOP with the help of physics classical mechanics. To test the accuracy of this system, an intermediate tech system of MOCAP is used to measure the dynamic motion of martial artists (silat) and non-martial artists. A standard operating procedure (SOP) was created to standardize the measurement. Using MOCAP system supplied by Motion Analysis, Cortex Motion Analysis (CMA) software and Osprey optical camera is used. 5 performers with experience in martial arts training (N ‘professional’, Z ‘Intermediate’, H ‘intermediate’) and non-experience in martial arts training (S and A). Measurement was done according to the SOP created according to another previous research. Divided into 5 parts the protocol was followed from the first protocol which is a construction of MOCAP, the second protocol is accuracy Testing, 3. Physical Evaluation, 4.